2012
DOI: 10.1038/nature11123
|View full text |Cite
|
Sign up to set email alerts
|

A signature of cosmic-ray increase in ad 774–775 from tree rings in Japan

Abstract: Increases in (14)C concentrations in tree rings could be attributed to cosmic-ray events, as have increases in (10)Be and nitrate in ice cores. The record of the past 3,000 years in the IntCal09 data set, which is a time series at 5-year intervals describing the (14)C content of trees over a period of approximately 10,000 years, shows three periods during which (14)C increased at a rate greater than 3‰ over 10 years. Two of these periods have been measured at high time resolution, but neither showed increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
611
2
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 461 publications
(645 citation statements)
references
References 24 publications
25
611
2
7
Order By: Relevance
“…Hambaryan & Neuhäuser (2013) suggested that a short hard Gamma-Ray-Burst could have caused the event, because all observables including the 14 C to 10 Be production ratio are consistent with such a burst. Eichler & Mordecai (2012) argued that a large solar flare cannot explain the event (as also argued in Miyake et al 2012), but an impact of a massive comet onto the Sun may be able to explain the energetics. Liu et al (2014) recently obtained additional 14 C measurements of corals off the Chinese coast, which have a much higher time resolution of, e.g., two weeks, while tree ⋆ E-mail: jessechapman@berkeley.edu rings have a one-year time resolution.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hambaryan & Neuhäuser (2013) suggested that a short hard Gamma-Ray-Burst could have caused the event, because all observables including the 14 C to 10 Be production ratio are consistent with such a burst. Eichler & Mordecai (2012) argued that a large solar flare cannot explain the event (as also argued in Miyake et al 2012), but an impact of a massive comet onto the Sun may be able to explain the energetics. Liu et al (2014) recently obtained additional 14 C measurements of corals off the Chinese coast, which have a much higher time resolution of, e.g., two weeks, while tree ⋆ E-mail: jessechapman@berkeley.edu rings have a one-year time resolution.…”
mentioning
confidence: 99%
“…They excluded supernovae as a possible cause due to the lack of any historic observations and of any young nearby supernova remnants, and they also excluded solar super-flares as a cause, because their spectra would not sufficiently explain the 14 C to 10 Be production ratio observed for that time. Then, Usoskin & Kovaltsov (2012), Melott & Thomas (2012), Thomas et al (2013), and Usoskin et al (2013) suggested that a solar super-flare beamed with only ≥ 24 • degree beam size could have caused the event (Melott & Thomas 2012), in particular if four to six times less 14 C was produced than calculated in Miyake et al (2012) due to a different carbon circulation model (Usoskin et al 2013). Hambaryan & Neuhäuser (2013) suggested that a short hard Gamma-Ray-Burst could have caused the event, because all observables including the 14 C to 10 Be production ratio are consistent with such a burst.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On timescales of 100 -1000 years, solar events such as the well-known Carrington event of 1859 and the 774/775 AD radiation burst (based on 14 C spike in tree rings) become important (Miyake et al 2012;Melott & Thomas 2012). 60 Fe deposits found on the ocean floor (multiple locations around the globe) as well as on the Moon, indicate the occurrence of multiple nearby supernovae within ∼100 pc from the solar system (Knie et al 2004;Binns et al 2016;Breitschwerdt et al 2016;Fimiani et al 2016;Wallner et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The possible impacts of superflares on space weather and terrestrial environment have been vigorously discussed (Miyake et al 2012;Schrijver et al 2012;Shibata et al 2013;Tsurutani & Lakhina 2014;Hayakawa et al 2015;Airapetian et al 2016;Takahashi et al 2016).…”
Section: Introductionmentioning
confidence: 99%